Tung oil as an effective modifier for sulfur polymer cement and its performance in galvanic waste encapsulation. Issue 5 (May 2020) - Banaszkiewicz, Kamil; Czechowski, Franciszek
Abstract: The data on the performance of sulfur polymer cement crosslinked with tung oil polymerization modifier are presented. Specimens of sulfur polymer cement (SPC) were prepared with different doses of tung oil in amounts of up to 8.85% of the sulfur mass. The obtained SPCs were used as binders to encapsulate two galvanic wastes differing in their toxic metal composition: waste I and waste II with loadings of approximately 25 and 50% of the composites' mass, respectively. For comparative purposes, appropriate samples of the SPCs and their composites with galvanic wastes were obtained using very similar doses of dicyclopentadiene sulfur modifier. Waste II was also encapsulated using SPC, in which a mixture of tung oil and dicyclopentadiene in a 1:1 weight ratio was used as the modifier. Crosslinking of the tung oil to the SPC matrix was assessed by FT-IR. The obtained SPCs and their composites with galvanic wastes were characterized by SEM and tested for water sorption capacity, compressive strength and metal leaching toxicity using TCLP and EN standards. The effectiveness of the tung oil binding to the SPC network was evidenced by the complete disappearance of methine C–H stretching vibrations at 3010 cm −1 and the double bond –C=C– wagging vibrations at 990 cm −1 in the FT-IR spectrum after processing with sulfur. SEM observations revealed that all the specimens prepared with dicyclopentadiene had a glassy-like fracture surface and also showed fewer cavities and defects in cements and composites when compared to their counterparts prepared with tung oil. The water sorption capacities of all the specimens were below 1%, where the values of those prepared with the tung oil were two to three fold higher than the values of their counterparts prepared with dicyclopentadiene. The pH of the TCLP leachates was in the range of 2.75–2.98, and a decreasing trend in the pH value was found with an increasing modifier dose. The TCLP leachate pH from the waste I monoliths with dicyclopentadiene were generally lower by 0.1–0.35 when compared to the corresponding monoliths with tung oil. The toxic metals immobilization order revealed from the TCLP test (leachate pH around 2.85) is Cd > Sr ≥ Zn > Cu > Ni > Cr > Pb, while the resulting order from the EN test, due to a higher leachate pH of about 5.9, follows Cd > Pb > Zn > Cu ≥ Ni > Sr > Cr. An increased tung oil dose from 2 to 8.85% enhanced the SPC compressive strength by three to four fold, while the same increase of the dicyclopentadiene dose led to an increase of this parameter for less than two fold. The addition of galvanic wastes to the SPCs resulted in a further increase in compressive strength for the corresponding SPC samples. Abstract : Civil engineering; Chemical engineering; Environmental engineering; Waste treatment; Environmental management; Waste; Tung oil; Sulfur polymer cement; Galvanic waste; Stabilization/solidification; Leaching test; Compressive strength.